2017
DOI: 10.1177/0276237417710762
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Camera Angle on Perception of Trust and Attractiveness

Abstract: Film theories have long proposed that the vertical camera angle influences how the scene and the character in it are interpreted. An elevated camera (high-angle shot) should diminish the qualities of the actor, whereas a lowered camera (low-angle shot) should elevate the actor in perspective as well as in the viewer's opinion. We were interested in how this holds up for the impression of trustworthiness and attractiveness that the spectator receives of the actor. We filmed 12 actors in a scenario inspired by a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
19
1
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 15 publications
3
19
1
3
Order By: Relevance
“…In contrast to our hypothesis, we did not find any effects of elevating or lowering the camera, neither for male (lowering the camera) nor for female faces (elevating the camera). However, this is in line with recent research by Baranowski and Hecht ( in press ) who did not find such an effect in faces of (unknown) actors.…”
Section: Studysupporting
confidence: 92%
See 1 more Smart Citation
“…In contrast to our hypothesis, we did not find any effects of elevating or lowering the camera, neither for male (lowering the camera) nor for female faces (elevating the camera). However, this is in line with recent research by Baranowski and Hecht ( in press ) who did not find such an effect in faces of (unknown) actors.…”
Section: Studysupporting
confidence: 92%
“…This conclusion is supported by findings that elevating the camera plus rotating the camera is generally preferred for taking selfies (Yeh and Lin, 2014 ; Kalayeh et al, 2015 ). An elevation within pure frontal depictions had no effect on attractiveness ratings at all what is in line with Study 1 and findings by Baranowski and Hecht ( in press ). However, there was a slight (but non-significant) decrease in perceived attractiveness.…”
Section: Studysupporting
confidence: 90%
“…The effects of camera position and angle have also been studied in the domain of film research in various experiment settings, often related to psychological factors, such as perceived social status, attractiveness, and trustworthiness (e.g., [3] and [15]). Camera angles have also been detected to affect dominance in video-mediated communication [8].…”
Section: Camera Height and Positionmentioning
confidence: 99%
“…This is useful because many effects can be achieved by changing the camera height (referred to as camera angle in traditional filmmaking). For example, experiments in film studies have shown that the camera angle can be used to convey feelings such as trustworthiness, attractiveness [3] [15], and dominance [8]. In 360° videos, camera height may affect the viewer's perception of self [16] [17], and may affect how content and the actors within this content are perceived [3]…”
Section: Camera Height In 360° Videosmentioning
confidence: 99%
“…Es más, hemos de considerar un continuum en las diferentes localizaciones de la cámara, por lo que en la práctica hay una gran cantidad de posiciones entre el mayor y el menor ángulo posible desde arriba y desde abajo, respectivamente (Maathuis, 2010), lo que hace que exista una gran heterogeneidad entre los ángulos de cámara empleados. Así, Baranowski y Hecht (2018), citan varios estudios realizados con ángulos que van desde los 9º a los 40º, comentando precisamente que esa diferencia en los ángulos utilizados complica aún más la interpretación de la evidencia empírica.…”
Section: Introductionunclassified